MODEL FOR RECRUITING SERVICEMEN IN THE ARMED FORCES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the decades of transition from conscript to professional armed forces, a number of unforeseen issues arose for the armed forces. One of the unresolved, but the most important and worrisome among them, is how the armed forces can attract and retain motivated personnel from the open labour market to fill the vacancy vacuum. Based on conducted research on the motivation of military personnel, the article examines a model for attracting them in the armed forces, analysing each of the elements that make it up and the interrelationships between them. This will contribute to enriching existing knowledge about work motivation and developing strategies for attracting and retaining military personnel.